Weekly Topotecan for Recurrent Ovarian, Fallopian Tube and Primary Peritoneal Carcinoma: Tolerability and Efficacy Study—The Israeli Experience. Issue 3 (1st March 2013) - Safra, Tamar; Berman, Tara; Yachnin, Adelya; Bruchim, Ilan; Meirovitz, Mihai; Barak, Frida; Atlas, Ilan; Levy, Tally; Rosengarten, Ora Solange
Abstract : Objectives: The purpose of this study was to assess the clinical activity and toxicity of weekly topotecan in a large cohort of epithelial ovarian (EOC), primary peritoneal (PPC), and tubal cancer patients. Methods: Records of patients with recurrent EOC, PPC, and tubal cancer who were treated with weekly topotecan (4.0 mg/m 2 on days 1, 8, and 15 on a 28-day cycle) after failure of more than 1 prior regimen were retrospectively reviewed in 8 centers in Israel. Results: Two hundred four patients were evaluated for efficacy and toxicity. Median age was 62 years (range, 27–89 years); 121 (59.3%) were platinum sensitive. Patients were exposed to a median of 2 previous lines (range, 1–9), and 48.5% received only 1 prior chemotherapy regimen. Median follow-up was 15.5 months (range, 2.5–112 months). Overall response rate was 26.5%, of which 11 patients (5.4%) had complete response, and 43 patients (21.1%) had partial response. Clinical benefit rate (complete response + partial response + stable disease) was 65.7%. Median progression-free survival was 4.0 months (95% confidence interval [CI], 3.5–4.5 months). There was no significant difference between platinum-sensitive and platinum-resistant patients regarding response rate or progression-free survival. Median overall survival from disease diagnosis was 45.0 months (95% CI, 40.04–49.6 months) and 16.0 months (95% CI, 12.3–19.7 months) from initiation of topotecan therapy. Overall survival was significantly different between patients with platinum-sensitive and platinum-resistant disease (19.9 vs 10.8 months, respectively, P = 0.003; 95% CI, 8.1–16.3 months). Multivariate analysis showed that only platinum sensitivity and topotecan line were associated with overall survival. Weekly topotecan was well tolerated—with only 16.7% of patients experiencing grade 3 to 4 hematologic toxicities. There were no other grade 4 toxicities, and only 6.9% grade 3 toxicities. Conclusions: In this large cohort of recurrent EOC, PPC, and tubal cancer, weekly topotecan was well tolerated with good clinical benefit rate, comparable to previous studies.